DEVELOPMENT AND OPTIMIZATION OF HYBRID SPACE FRAME RACE CAR CHASSIS - ADINAN, MUHAMAD FAIZAL (2018)
In process of nurturing future engineer, Formula Society of Automotive Engineers (FSAE) competition is held for various academic institutions to compete with each other to design the best FSAE race car. FSAE race car is similar to a typical Formula one race car, open cockpit, single seated and open wheel. The major difference between FSAE and Formula One race car is the specifications of the car. The other difference is the rules, throughout this study, FSAE rules will be used as a primary reference. For any race car, in this case, FSAE race car, the winning recipe in the competition is to have a low weight and high stiffness chassis. Unfortunately, these two factors are contradicted with one another and therefore give existence for this study to harmonized these factors into one competent chassis. This study shall discuss about hybrid chassis with a front monocoque and rear space frame that complement each other. Knowledge such as chassis engineering and vehicles dynamics as well as designing skills are crucial for the completion of this study. With these knowledge and skills equipped, a light-weighted, stronger and safe. While having different approach on designing and manufacturing the car, each team always thrive for low weight but strong material to build the car. As technology advanced, as for monocoque chassis, a structure known as honeycomb sandwich have been introduced. This structure provides lightweight but at the same time is very strong. As for space frame, the material selection is also important to reduce weight but increase strength and further optimization to provide optimum results. To fully evaluate the designed chassis, ANSYS simulation is done based on the requirement by the rules. Major simulation required by the FSAE committee is the impact test, torsional turbidity and the chassis capability to withstand the static loads. The result would later be compared with other available designs in terms of weight and strength towards deformation. This is to validate the capabilities of the designed chassis by using benchmarking.